2021
DOI: 10.1002/onco.13830
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Neratinib Plus Capecitabine in the Subgroup of Patients with Central Nervous System Involvement from the NALA Trial

Abstract: Background.Neratinib has efficacy in central nervous system (CNS) metastases from HER2-positive metastatic breast cancer (MBC). We report outcomes among patients with CNS metastases at baseline from the phase III NALA trial of neratinib plus capecitabine (N + C) versus lapatinib plus capecitabine (L + C). Materials and Methods. NALA was a randomized, activecontrolled trial in patients who received two or more previous HER2-directed regimens for HER2-positive MBC. Patients with asymptomatic/stable brain metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…Further insights were provided by the randomized phase 3 NALA trial that has confirmed that intracranial objective response rate, PFS and OS were higher in patients with BM treated with neratinib plus capecitabine (26.3%; 7.8 months; 16.4 months) as compared with patients who received lapatinib plus capecitabine (15.4%; 5.5 months; 15.4 months) [ 9 ]. Furthermore, neratinib plus capecitabine as compared with lapatinib and capecitabine was also associated with a longer PFS (12.4 months vs. 8.3 months), and lower cumulative incidence of interventions for CNS disease (25.5% vs. 36.0%), and progressive CNS disease (26.2% vs. 41.6%), suggesting that such a combined treatment could be a valuable option in patients with CNS involvement from HER2-positive metastatic BC [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further insights were provided by the randomized phase 3 NALA trial that has confirmed that intracranial objective response rate, PFS and OS were higher in patients with BM treated with neratinib plus capecitabine (26.3%; 7.8 months; 16.4 months) as compared with patients who received lapatinib plus capecitabine (15.4%; 5.5 months; 15.4 months) [ 9 ]. Furthermore, neratinib plus capecitabine as compared with lapatinib and capecitabine was also associated with a longer PFS (12.4 months vs. 8.3 months), and lower cumulative incidence of interventions for CNS disease (25.5% vs. 36.0%), and progressive CNS disease (26.2% vs. 41.6%), suggesting that such a combined treatment could be a valuable option in patients with CNS involvement from HER2-positive metastatic BC [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 6 Patients in the neratinib arm experienced improved PFS and CNS outcomes, but similar OS when compared with those treated with lapatinib. 26 Finally, in addition to their use as a treatment for established BM, there is growing interest in the use of TKIs such as neratinib as a means of preventing or delaying the occurrence of BM in patients with early 27 or metastatic 15 BC.…”
Section: Discussionmentioning
confidence: 99%
“…Among these two patient cohorts, median PFS was 5.5 and 3.1 months, respectively, and median OS was 13.3 and 15.1 months, respectively, though no direct comparisons between groups were reported ( 109 ). When compared head-to-head with lapatinib and capecitabine (L+C) in a recent RCT, neratinib and capecitabine (N+C) showed a substantial though not statistically significant effect on OS (13.9 vs. 2.4 months, HR 0.90, p=0.635) and PFS (5.6 vs. 4.3 months, HR 0.66, p=0.074) in HER2-positive breast cancer patients with IMD who have previously failed at least two anti-HER2 therapies ( 110 ). The lack of statistical significance may have been due to small sample sizes.…”
Section: Emerging Treatments For Imdmentioning
confidence: 99%